Pengaruh Cerita Pendidikan “Semut Dan Jangkrik” Terhadap Perkembangan Moral Anak Usia 5-6 Tahun - Afifa, Nida; Handayani, Peny Husna (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
Fable story books can be used as a learning activity for children and as an instillation of children's moral behavior which is given by teachers to children from an early age as a trigger for children when they be have badly. Inthiscase, there is a lack of storytelling activities in instilling moral values in children. This research aims to determine the influenceof the story "Ants and Crickets" on the moral development of early childhood. This research is to improve moral development, especially in the aspects of empathy, self- control andtolerance. Thistypeof research is quantitative experimental with a research design, namely The Equivalent Time Samples Design.The research instrument used was an observation sheet. The research results in this study showed that the 1 0samp lesobtained sign ificant result swith A sympvalues .Sigis 0.005 because the valueis <0.05, so the hypothes is accepted, namely the result softhe hypothesis test show that the storyof Ants and Jangkrik has an effect on the moral development of children aged 5-6 years. The conclusion of this research is that there is a significant influence of the story "Ants and Jangkrik" on the moral development of children aged 5-6 years.